126 Pharmacodynamics of rituximab on B cells in paediatric post-HSCT patients with EBV. (22nd November 2019) - Perinparajah, Soumya; Silva, Juliana; Worth, Austen; Cheung, Amy; Yates, James; Klein, Nigel; Breuer, Judith; Veys, Paul; Amrolia, Persis; Standing, Joseph
Abstract : Aims: Rituximab is a chimeric IgG-1 monoclonal antibody that depletes B cells, and is prescribed off-label to children. Due to its mechanism of action, it is given for Epstein Barr virus (EBV), which is commonly reactivated after haematopoietic stem cell transplantation (HSCT). This study aims to identify the pharmacodynamics of rituximab in children with EBV post-HSCT to optimise the dose. Methods: Retrospective electronic data were collected from children who underwent HSCT at a tertiary paediatric hospital between 2005 and 2017, and were prescribed rituximab for EBV post-HSCT; data were provided by the GOSH Digital Research Environment (DRE) team. Intravenous infusions of rituximab were administered at a dose of 375 mg/m 2 weekly for either one week or four weeks. Rituximab pharmacokinetics were not available, but CD19 + B cell counts were available before and after rituximab treatment. A modified version of a previously described kinetic-pharmacodynamic (K-PD) turnover model was applied, and time to age-specific CD19 + B cell reconstitution was compared between patients given a single dose or four doses of rituximab. Results: 683 measurements of CD19 + B cell counts were available from 55 children who received rituximab for EBV post-HSCT. The median time to reconstitution was 267 days and 370 days in patients administered a single dose (n=39) and four doses (n=16) of rituximab respectively. A slower rate of reconstitution was observed for the four-dose group than for the single-dose group, although not significant. The K-PD model described the time course of CD19 + B cells well following treatment with rituximab. The final parameter estimates are summarised in table 1 . Conclusions: The model adequately describes CD19 + B cell dynamics in response to rituximab. Model refinements will include addition of a covariate model and incorporating EBV data to better understand the dynamics of viral inhibition in this population to ultimately inform rituximab dosing.